PENGARUH KUALITAS LAYANAN TUTORIAL ONLINE TERHADAP KEPUASAN DAN LOYALITAS MAHASISWA FISIP-UT - Frans, Yudith A; Aisyah, Siti (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2018)
As students of distance education institutions, the interest of Universitas Terbuka’s students in following the online tutorials  showed an increasing number from year to year. However, the number of students who actively following the online tutorial apparently not as big as the number of students who activated the tutorial.  This showed that there were certain factors that caused students did not participate actively. A quantitative approach was used to explain the effect of online tutorial service quality on students’ satisfaction and loyalty. Data collected through an online survey to all participants in the Faculty of Law, Social and Political Sciences (FISIP) which selected using accidental sampling technique. Furthermore, the data was analyzed by using the regression analysis and the univariate analysis. These analyses showed that the SERVQUAL model could be used to measure the learning services quality from multidimensional. Learning support services via the Internet (online tutorial) provided by UT stated in the good and satisfactory category. However, there were aspects of learning support services that still needed to be fixed by Universitas Terbuka, especially the accuracy of tutorial services provided by tutors, the speed of time to respond, giving feedback, and answering student questions.